Muslims of northern Mozambique and the liberation movements - Bonate, Liazzat J. K. (Social Dynamics, 2009)
Despite the fact that the liberation war occurred in northern Mozambique, where a considerable number of Muslims lived, their contribution to the independence struggle has been little studied. This paper focusses on their participation in two nationalist liberation movements, Mozambican African National Union (MANU) and Frente de Libertação de Moçambique (FRELIMO), and demonstrates that the prevailing idea in scholarship about Muslims’ aloofness from the liberation struggle is unjustified. It argues that Muslim support and participation in the liberation movements stemmed primarily from grassroots African nationalism. Like most Africans, Muslims wished to end colonialism and recover their land from the Portuguese. African Muslims of northern Mozambique were well suited to support these movements, because Islam and chieftainship were linked to each other. Chiefs were believed to be the ‘owners’ and ‘stewards’ of the land, and a majority of Muslim leaders, whether traditional chiefs (régulos, in Portuguese) or Sufi leaders (tariqa khulafa’, in Arabic), were from the chiefly clans. Most importantly, Muslims of northern Mozambique had close historical and cultural ties to Tanganyika and Zanzibar, especially through Islamic and kinship networks. The involvement of Muslims in the liberation movements of those regions, in particular in Tanganyika African National Union (TANU), inspired and encouraged the Muslims of northern Mozambique to support MANU and FRELIMO, especially since these two movements were launched in Tanganyika and Zanzibar with TANU backing and the participation of Muslim immigrants from northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Youth exclusion, violence, conflict and fragile states - Hilker, Lyndsay McLean; Fraser, Erika (Social Development Direct, 2009)
This report forms part of a portfolio of work on youth focussed on two interconnected thematic areas: youth, jobs and growth and on youth exclusion, fragile states and conflict and complements work being conducted to develop a Youth Participation Guide for DFID staff. It is intended to inform a DFID Policy Briefing and a practical Guidance Note on addressing youth exclusion and unemployment. The objectives of the study are: (i) To scope out existing evidence and analysis on the links between youth exclusion, violence, conflict and fragile states and distil this information to enable DFID (and partners) to better understand the implications for poverty elimination, state and community-building, peace-building, Disarmament, Demobilisation and Reintegration (DDR) and conflict prevention, in order to address the issues more effectively in policy and programmes; (ii) To develop a conceptual framework that renders this information manageable while still reflecting the many dimensions of this issue. The study involved a desk-based literature review and consultations with a small number of key informants from DFID, other donors, academia and youth groups. This study focuses mainly on people aged 15-24, but conceptualises “youth” as a transitional stage in life between childhood and adulthood rather than as a rigid construct based on age. It recognises the diversity of youth by gender, class, ethnicity and focuses on the multiple dimensions of exclusion that systematically disadvantage youth. It also takes a holistic approach to violence – recognising that in practice different forms of violence (e.g. political, criminal, interpersonal, extremism) may overlap and that some of the same structural and proximate factors may drive youth engagement in different forms of violence.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude